Murur Scheme Educational Model: An Andragogy-Based Innovation for Strengthening Hajj Moderation - Jajat, Dede; Salam, Abdus; Karim, Abdul (Scaffolding: Jurnal Pendidikan Islam dan Multikulturalisme, 2025)
The purpose of this study was to construct an educational model for strengthening religious moderation among elderly Hajj pilgrims at the Hajj and Umrah training institution of the Nurulhuda Islamic Education Foundation in Ciamis. This research approach used a qualitative case study method. Data collection was carried out through semi-structured interviews with the Foundation Leader, Ustadz, and elderly Hajj pilgrims. As well as observations through observing Hajj training activities for the pilgrims. Data analysis used the Miles and Huberman model, and validity testing used a data credibility test with the triangulation method. The results of the study showed: 1)Murur Scheme Education was carried out with the following schemes: Delivery of Murur policies, Socialization of new aspects in Murur policies in Muzdalifah, Comprehensive understanding of elderly pilgrims, and innovating ways to provide a correct understanding regarding the obligatory Hajj. 2)Strengthening Andragogy-Based Hajj Moderation was carried out by strengthening religious moderation in accompanying Hajj pilgrims, providing provisions before Hajj departure, during Hajj implementation, and after the peak of Hajj. 3)Implementation is carried out through the application of andragogy, through education by tutors, organization of learning materials, and learning methods. 4)Implications of Andragogy-Based Murur Scheme Education through two phases, namely, the education phase and the Andragogy-Based Hajj Moderation Strengthening Phase. The results of the study contribute by providing innovative solutions for elderly Hajj education through an andragogy approach that can be adopted by educational institutions and Hajj organizers, and support the development of a more inclusive and adaptive learning model.